2000
DOI: 10.1557/proc-663-115
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Cement Hydrates by Radionuclide Sorption Mechanism

Abstract: A categorization of cement components was attempted from the viewpoints of their chemical constituents and sorption behaviors. In this study, we assumed that the cement components are categorized into four groups, calcium silicate compounds, hydroxides, calcium aluminate compounds, and others. The sorption behaviors were compared among the four groups by batch sorption experiments carried out for 12 kinds of cement components using the radionuclides cesium, iodine, inorganic carbon, and nickel as different che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…The ‘0D’ in the sample notation represents 0 days leaching. The trace for the blank cement sample without waste simulants (sample B) shows the formation of calcium silicate hydrate (C–S–H), portlandite (CH), hydrotalcite (Hc) and monosulphoaluminate (AFm) as expected from the literature 1,3,4,8 in addition to the gehlenite (G) contained in the original BFS.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…The ‘0D’ in the sample notation represents 0 days leaching. The trace for the blank cement sample without waste simulants (sample B) shows the formation of calcium silicate hydrate (C–S–H), portlandite (CH), hydrotalcite (Hc) and monosulphoaluminate (AFm) as expected from the literature 1,3,4,8 in addition to the gehlenite (G) contained in the original BFS.…”
Section: Resultssupporting
confidence: 53%
“…The results show that the introduction of CsNO 3 and/or Sr(NO) 3 have different impacts on the cement phases formed in the system. X-ray diffraction and SEM indicates that the majority of the CsNO 3 was not associated with any other phases.…”
Section: Incorporation Of Cs and Srmentioning
confidence: 96%
See 1 more Smart Citation
“…1. The results regarding the adsorption behavior of Cs on C-S-H with varying C/S ratios are consistent with the results reported by Noshita et al (2000) and Ochs et al (2006). Conversely, the C/S ratio of C-S-H was found to have nearly no effect on the adsorption of Sr on C-S-H, which suggests a difference between the adsorption behaviors of Sr and Cs on C-S-H.…”
Section: Modeling Of Interaction Of C-s-h With Cs and Sr Ionssupporting
confidence: 90%
“…The adsorption amount of Cs, which like Na and K is a monovalent cation, increases in the same manner as that of Na and K when the C/S ratio decreases (Faucon et al 1997;. The coexistence of Na and K has also been reported to affect the adsorption behavior of Cs because of the competitive adsorption among them (Noshita et al 2000;Viallis et al 1999;Viallis-Terrisse 2000;Viallis-Terrisse et al 2001). Conversely, with regard to divalent Sr, it has been reported that the solid-to-liquid ratio and the C/S ratio of C-S-H as well as the Ca and Sr concentrations in the aqueous phase affect the adsorption of Sr on C-S-H (Tits et al 2004(Tits et al , 2006Wieland et al 2008;.…”
Section: Introductionmentioning
confidence: 99%